Lithium ion transport in solid polymer electrolyte filled with alumina nanoparticles. (1st April 2022) - Wang, Jiaqi; Fan, Linhao; Du, Qing; Jiao, Kui
Abstract : The addition of Al2 O3 enhances Li + transport along the PEO chains and provides an additional Li + transport path, thereby significantly improving the conductivity. Abstract : Using a solid polymer electrolyte (SPE) is a promising approach for improving lithium battery durability by suppressing the growth of lithium dendrites. However, the low conductivity at room temperature significantly limits its commercial application. In this work, Al2 O3 nanoparticles are used as a filler in a SPE with polyethylene oxide (PEO) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt to improve its conductivity, and the resulting structure and transport properties are analyzed in detail using molecular dynamics simulations. The results show that the addition of Al2 O3 nanoparticles decreases the crystallinity and increases the degree of order of the PEO chains and makes it easier for Li + to combine with the PEO chains, thereby significantly enhancing Li + transport along the PEO chains. Moreover, the addition of Al2 O3 provides an additional Li + transport path, which is the interface between the Al2 O3 and PEO chains. Therefore, after adding Al2 O3 nanoparticles, the conductivity is increased by 192.25% and 248.94% at 333 and 300 K, respectively, for the SPE with shorter PEO chains and by 225.2% and 285% at 333 and 300 K, respectively, for the SPE with longer PEO chains. Moreover, the enhancement effects of Al2 O3 nanoparticles on conductivity are more significant for SPEs with longer PEO chains at lower temperatures.